Prevalence, care-seeking practices and impact of self-reported vision impairment in Southwest Cameroon: a community-based study. Issue 11 (26th November 2020) - Mbeboh, Susan N; Christie, Sabrinah Ariane; Carvalho, Melissa; Dickson, Drusia; Nana, Theophile; Embolo, Frida; Dicker, Rochelle; Juillard, Catherine; Chichom Mefire, Alain
Abstract : Objectives: To establish the prevalence of self-reported vision impairment (VI) in Southwest Cameroon and describe associated care-seeking practices, functional limitations and economic hardships. Design: A three-stage clustered sampling household community-based survey. Setting: The Southwest region of Cameroon. Participants: 8046 individuals of all ages residing in the Southwest region of Cameroon. Primary and secondary outcome measures: Prevalence of self-reported VI, onset of vision loss, care-seeking practices, diagnosis and treatment, functional limitations, economic hardships on household, beliefs about surgical treatability of blindness and barriers to surgical care. Results: The estimated prevalence of self-reported VI in Southwest Cameroon was 0.87% (95% CI 0.62 to 1.21). Among participants aged ≥40 years, the prevalence increased to 2.61% (95% CI 1.74 to 3.90). Less than a quarter of affected participants reported difficulty working (20.5%) or trouble going to school (12.0%) as a result of their VI. Yet, over half (52%, n=43) of affected households experienced significant economic hardships due to the VI. Residing in an urban setting (aOR 1.16, 95% CI 1.04 to 1.30) and belonging to a higher socioeconomic status (aOR 1.13, 95% CI 1.02 to 1.26) were factors associated with the belief that certain types of blindness were surgically reversible. Formal care was not sought by 16.3% (n=8) of affected participants. Cataracts was the leading diagnosis among participants who did seek formal care (43.2%, n=16), although 93.8% of these cases were not surgically treated, primarily due to a lack of perceived need. Conclusion: The prevalence of individuals who report vision impairment in Southwest Cameroon is considerably lower than prior published estimates based on visual physical examinations. Routine community-level screening and cost financing schemes could improve detection of pre-clinical eye disease and the utilisation of surgical care. It could also pre-empt disability and economic hardships associated with advanced VI in the region.